An Analysis of Powers and Duties of a Receiver under Nigerian Company Law - Michael Takim Otu; Miebaka Nabiebu (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
The law draws a distinction between the functions of a receiver and a manager. A receiver has the duty to stop the business, collect the debts and realize the assets. He has no authority to carry on a going concern. Nevertheless, a manager, on the other hand, has powers to continue a business or any going concern. Thus, the primary motive for the appointment of the receiver/manager is that of the realization and preservation of the company’s security of those on whose behalf he is appointed. The actual role of a receiver is that of an agent. He as an agent is personally liable on any contract entered into by him in the performance of his functions except where the contract provides otherwise. As an agent, the primary duties of the receiver involve good faith, special confidence, and candour towards another. Basically, the duties of a receiver are those which can justifiably be said to be incidental to his powers of management. The paramount duty of the receiver on his appointment is to take possession of all the assets covered by the charge, since those are the things he is appointed to manage with a view to recovering what may be due to the debenture holders or mortgagees.